The Effect of Ethanol Extract of Miana Leaves (Plectranthus scutellarioides (L.) Benth.) on the Viability of Human Gingival Fibroblasts - Muhammad Rizqi; Bambang S Trenggono; Fathimah Azzahra Attamimi; Siti Nur Riani (Syntax Literate, 2026)
Miana leaves (Plectranthus scutellarioides (L.) Benth.) are herbal plants containing bioactive compounds such as flavonoids, tannins, saponins, and alkaloids that potentially exhibit antibacterial and anti-inflammatory activities in dentistry. However, the safety of herbal materials on normal cells needs to be evaluated, including gingival fibroblasts which play an important role in wound healing and tissue regeneration. To determine the effect of ethanol extract of miana leaves on the viability of human gingival fibroblasts at various concentrations and to review its potential utilization from an Islamic perspective. This study was an in vitro experimental laboratory study. Human gingival fibroblast cells were cultured using DMEM medium and treated with ethanol extract of miana leaves at concentrations of 12.5, 25, 50, 100, and 200 µg/mL. The control groups consisted of solvent control, untreated control, and 10% DMSO control. Cell viability was assessed using the Cell Counting Kit-8 (CCK-8) method. Data were analyzed using Kruskal–Wallis test, Post Hoc Mann–Whitney test, and Spearman correlation analysis. The mean viability of gingival fibroblasts at concentrations of 12.5, 25, 50, 100, and 200 µg/mL were 121.48%, 116.69%, 117.09%, 117.09%, and 113.35%, respectively. The Kruskal–Wallis test showed a significant difference between the treatment and control groups (p0.05). There were differences in the viability of human gingival fibroblasts after treatment with ethanol extract of miana leaves, with a tendency for cell viability to decrease as the extract concentration increased.